Issues in mathematics teaching - Gates, Peter (b)
The contributors look at a range of issues in the teaching of mathematics that will enable students to build upon their learning and place their teaching into a wider context. This book presents the key debates that the mathematics teacher will need to understand, reflect on and engage in as part of their professional development. Issues in Mathematics Teaching is suitable for those at initial training level right through to practising mathematics teachers. Its accessible structure enables the reader to pursue the issues raised as each chapter includes suggestions for further reading and questions for reflection or debate.
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching -- Great Britain; MATHEMATICS -- Study & Teaching